Eksperimentasi Model Pembelajaran Kooperatif Think Pair Share (TPS) Dengan Pendekatan Realistic Mathematics Education (RME) Terhadap Hasil Belajar Matematika Siswa Kelas VII Mts N 4 Bojonegoro - Iin Sevya; Budi Sasomo; Amiratih Siti Aisyah (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This study seeks to identify learning models that affect students' mathematics learning outcomes. Students at MTs N 4 Bojonegoro have poor or low learning outcomes, especially in Line and Corner material, because the indicators of the learning process at the school have not been optimal. One of the learning models that can be used is the Think Pair Share (TPS) Cooperative Learning model with the Realistic Mathematics Education (RME) Approach. This quantitative experimental research uses Postest only Control Design, with three samples selected using Cluster Random Sampling, two classes as the experimental class and one class as the control class, and using one class, namely class VII E as the test class. The samples have been distributed normally and homogeneously. Data analysis uses anava and post-anava tests. Think Pair Share (TPS) with the Realistic Mathematics Education (RME) Approach produced an average of 76.67, while TPS alone produced an average of 70.81 and the conventional learning model produced an average of 62.42. Students who are taught using the Think Pair Share (TPS) model with the Realistic Mathematics Education (RME) Approach obtained a better average and outperformed students who were taught using the TPS model alone or conventional, as the calculation of this study obtained Fcal > Ftabel with a value of Fα = 10.09 and a value of Ftabel = 3.1.